Efficacy of anti-obesity medication (AOM) and endoscopic gastric remodeling (EGR): Analysis of combination therapy with optimal timing and agents - Jirapinyo, Pichamol; Jaroenlapnopparat, Aunchalee; Thompson, Christopher C. (Endoscopy International Open, 2024)
Background and study aims Endoscopic gastric remodeling (EGR) and anti-obesity medications (AOMs) are effective weight loss therapies. While the efficacy of EGR and AOMs has been established, the effect of combination therapy and its optimal approach remain unknown.Patients and methods This was a single-center retrospective review of prospectively collected data from patients who underwent EGR. Patients were categorized as: 1) monotherapy – EGR alone; 2) combination therapy – an AOM prescribed within 6 months of EGR; and 3) sequential therapy – an AOM prescribed greater than 6 months of EGR. Outcomes included percent total weight loss (%TWL) at 12 months, response rate (≥ 10%TWL at 12 months), and serious adverse event rate.Results A total of 208 patients were included. Of them, 65 (34%), 61 (31%), and 82 (35%) underwent monotherapy, combination therapy, and sequential therapy, respectively. At 12 months, patients who received EGR+GLP-1RA combination therapy achieved the greatest weight loss (23.7±4.6% TWL), while those who began with AOM followed by EGR more than 6 months later had the lowest weight loss (12.0±7.7%TWL) compared with monotherapy (17.3±10.0% TWL) (P = 0.04 and 0.03, respectively). The response rate was 100% for EGR+GLP-1RA combination therapy and 56% for AOM followed by EGR sequential therapy (P = 0.02).Conclusions Combining AOM with EGR appears to result in greater weight loss compared with other strategies, with GLP-1RA as the preferred agent and optimal initiation of both therapies occurring within 6 months of each other. Prolonged medication use prior to EGR appears to be associated with suboptimal weight loss, suggesting the importance of early referral for adjunctive therapy.
Keywords: GI surgery; Endoscopy Upper GI Tract; Reflux disease; Quality and logistical aspects; Performance and complications